Promoter and domain structures regulate FLA12 function during Arabidopsis secondary wall development - Ma, Yingxuan; Ratcliffe, Julian; Bacic, Antony; Johnson, Kim L. (Frontiers in Plant Science, 2023)
Introduction Fasciclin-like arabinogalactan-proteins (FLAs) are a family of multi-domain glycoproteins present at the cell surface and walls of plants. Arabidopsis thaliana FLA12 and homologs in cotton, Populus, and flax have been shown to play important functions regulating secondary cell wall (SCW) development. FLA12 has been shown to have distinct roles from the closely related FLA11 that also functions during SCW development. The promoter and domain features of FLA12 that regulate functional specificity have not been well characterized. Methods In this study, promoter swap experiments of FLA11 and FLA12 were investigated. Mutation of proposed functional regions within FLA12 were used to investigate the role of post-translational modifications on sub-cellular location and trafficking. Domain swap experiments between FLA11 and FLA12 were performed to identify regions of functional specificity. Results Promote swap experiments showed that FLA12 is differentially expressed in both stem and rosette leaves compared to FLA11. Post-translational modifications, in particular addition of the glycosylphosphatidylinositol-anchor (GPI-anchor), were shown to be important for FLA12 location at the plasma membrane (PM)/cell wall interface. Domain swap experiments between FLA11 and FLA12 showed that the C-terminal arabinogalactan (AG) glycan motif acts as a key regulatory region differentiating FLA12 functions from FLA11. Discussion Understanding of FLA12 promoter and functional domains has provided new insights into the regulation of SCW development and functional specificity of FLAs for plant growth and development.